Molecular Detection of Antibiotic-Resistant Genes in Pseudomonas aeruginosa from Nonclinical Environment: Public Health Implications in Mthatha, Eastern Cape Province, South Africa - Mojisola Clara Hosu; Sandeep Vasaikar; Grace Emily Okuthe; Teke Apalata (International Journal of Microbiology)
Evaluation of resistant profiles and detection of antimicrobial-resistant genes of bacterial pathogens in the nonclinical milieu is imperative to assess the probable risk of dissemination of resistant genes in the environment. This paper sought to identify antibiotic-resistant genes in Pseudomonas aeruginosa from nonclinical sources in Mthatha, Eastern Cape, and evaluate its public health implications. Samples collected from abattoir wastewater and aquatic environment were processed by membrane filtration and cultured on CHROMagarTM Pseudomonas medium. Species identification was performed by autoSCAN-4 (Dade Behring Inc., IL). Molecular characterization of the isolates was confirmed using real-time polymerase chain reaction (rPCR) and selected isolates were further screened for the possibility of harboring antimicrobial resistance genes. Fifty-one Pseudomonas species were recovered from abattoir wastewater and surface water samples, out of which thirty-six strains were Pseudomonas aeruginosa (70.6%). The P. aeruginosa isolates demonstrated resistance to aztreonam (86.1%), ceftazidime (63.9%), piperacillin (58.3%), cefepime (55.6%), imipenem (50%), piperacillin/tazobactam (47.2%), meropenem (41.7%), and levofloxacin (30.6%). Twenty out of thirty-six P. aeruginosa displayed multidrug resistance profiles and were classified as multidrug-resistant (MDR) (55.6%). Most of the bacterial isolates exhibited a high Multiple Antibiotic Resistance (MAR) Index ranging from 0.08 to 0.69 with a mean MAR index of 0.38. In the rPCR analysis of fifteen P. aeruginosa isolates, 14 isolates (93.3%) were detected harboring blaSHV, six isolates (40%) harbored blaTEM, and three isolates (20%) harbored blaCTX-M, being the least occurring ESBL. Results of the current study revealed that P. aeruginosa isolates recovered from nonclinical milieu are resistant to frontline clinically relevant antipseudomonal drugs. This is concerning as it poses a risk to the environment and constitutes a public health threat. Given the public health relevance, the paper recommends monitoring of multidrug-resistant pathogens in effluent environments.